CSF biomarkers for Alzheimer Disease are associated with spatial cognition in cognitively normal older adults. (20th December 2022) - Coughlan, Gillian T; DeSouza, Brennan; Zhukovsky, Peter; Hornberger, Michael; Grady, Cheryl; Buckley, Rachel F.
Abstract: Background: Spatial cognition has emerged as a promising cognitive fingerprint for the detection of Alzheimer's disease (AD). Despite evidence that spatial cognition is highly sensitive to AD dementia and is apparent even in adults at‐genetic‐risk of AD, the association between spatial cognition and AD biomarkers in cognitively normal adults is unknown. Method: This study leverages data from the European Prevention of Alzheimer's Dementia Consortium, a multinational observational study of clinically normal adults initiated in 2016 that includes two digital spatial paradigms: The Supermarket Task (SMT)and the Four Mountains Task (4MT;Fig1). Using a mixed model approach with random intercepts, we investigated cross‐sectional associations between cerebrospinal fluid (CSF) β‐amyloid1‐42 (Aβ1‐42 ) and phosphorylated tau (p‐tau181 ) with task performance (N = 1672; mean age = 68.08[SD = 6.96]). Result: Five hundred and forty‐nine (32.8%) participants had abnormal levels of CSF Aβ1‐42 and p‐tau181 . Across the whole sample, higher p‐tau181 concentrations were associated with greater spatial disorientation from the starting location on the SMT (r = ‐0.449, p = <0.001). There was a small association with CSF Aβ1‐42 (r = 1.984, p = 0.003; Fig2A‐B). Higher levels of CSF p‐tau181 were associated with more 4MT feature memory errors (r = ‐0.570, p<0.001). There was also a main effect of Aβ1‐42 on 4MT performance (r = 0.301, p = <0.001; Fig2C‐D). Entorhinal cortex and hippocampal volumes both predicted better performance on both tasks (r's = 0.37‐0.57; Fig3). Post hoc analyses revealed a significant interaction between sex and hippocampal volume, indicating that the association between hippocampal volume and recall of environmental features was stronger in males than females. Finally, volume of the entorhinal cortex, but not the hippocampus, mediated the relationship between p‐tau181 and performance on both spatial tasks (Fig4). Conclusion: Our results suggest that spatial tasks are sensitive to CSF p‐tau181 and to a lesser extent Aβ1‐42 in preclinical AD. Given the well‐validated digital platform that these tasks are founded on, these tools provide access to racially and ethnically diverse individuals for preclinical AD trial registries via unsupervised assessment.